Diurnal Variations in the First 24/7 Mobile Stroke Unit. Issue 7 (July 2019) - Zaidat, Osama O.; Changal, Khalid H.; Sultan-Qurraie, Ali; de Havenon, Adam; Calderon, Victoria J.; Goins-Whitmore, Julie; Patterson, Mary S.; Lin, Eugene
Abstract : Background and Purpose—: Mobile Stroke Units (MSUs) provide innovative prehospital stroke care but their 24/7 operation has not been studied. Our study investigates 24/7 MSU diurnal variations related to transport frequency, patient characteristics, and stroke treatments. Methods—: We compared transportation frequency, demographics, thrombolytic and mechanical thrombectomy administration, and treatment metrics across 8-hour shifts (morning, evening, and nocturnal) from our 24/7 MSU in Northwest Ohio prospective database. Results—: One hundred ninety-five patients were transported by the MSU. Most transports occurred during the morning shift (52.3%) followed by evening shift (35.8%) and nocturnal shift (11.9%; P trend <0.001). Twenty-three patients (11.9%) received intravenous thrombolytic in the MSU, most frequently in the morning shift (56.5%). No cases of mechanical thrombectomy were performed on MSU patients in the nocturnal shift. Conclusions—: Morning and evening shifts account for the majority of our MSU transports (88.1%) and therapeutic interventions. Understanding temporal variations in a resource-intensive MSU is critical to its worldwide implementation.